77 CUTOFF VALUE OF SERUM C-REACTIVE PROTEIN ON THE FIFTH POSTOPERATIVE DAY IS EFFECTIVE TO RULE OUT ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY. (14th September 2020) - Hubaud, V; Bottet, B; Chenesseau, J; Gust, L; Bouabdallah, I; Brioude, G; Trousse, D; Thomas, P; D'journo, X
Abstract:  : Anastomotic leakage is one of most severe complications after esophagectomy. There is no consensus on the best method of identification of such complications. Serum C-reactive protein measurement on postoperative day 5 (POD) has been reported to be reliable to rule-out leakage. Methods: We prospectively assessed the medical records of consecutive post-esophagectomy patients from January 2019 to January 2020. We analyzed serum CRP and complete blood cell counts from the day before surgery to the POD5. A CRP level ≤ 150 mg/l at POD5 was considered sufficient to start oral feeding. In contrast a CRP level > 150 mg/l at POD5 lead to a computed tomography (CT) with oral contrast to rule-out the presence of an anastomotic leakage. Anastomotic leakage was classified according to ECCG classification. Sensibility, sensitivity, positive and negative predictive value of CRP were calculated. Results: Over a 12-month period, 52 patients were included (Figure 1). Measurement of CRP on POD5 was ≤150 mg/l in 34 (64%) patients (32 without fistula and 2 with fistula diagnosed after POD5) and > 150 mg/L in 18 (36%) patients (8 without fistula and 10 with fistula). Twelve (23%) patients developed anastomotic fistula. The cutoff value of CRP ≤150 mg/l on the POD5 was associated with sensitivity 83%, specificity 80%, positive predictive value 56% and negative predictive value 94%. The CRP protocol allowed to avoid 30/52 (57%) unnecessary postoperative CT-scan. Conclusion: On the basis of a high negative predictive value, a CRP level at POD5 ≤ 150 mg/l can be effective to eliminate an anastomotic leakage and to start oral feeding without any further exams. This information is useful in the context of ERAS protocols to reduce hospital discharge and decrease hospital costs.